2008
DOI: 10.3113/fai.2008.0124
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Results of Our First 49 Scandanavian Total Ankle Replacements (STAR)

Abstract: Our results are comparable with those reported in the literature. The clinical outcome improved significantly. Due to aseptic and septic loosening, 8.2% of the prosthesis failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 12 publications
3
44
2
3
Order By: Relevance
“…Other reports with similar findings have been published afterwards (Besse et al, 2009;Besse et al, 2010;Kokkonen et al, 2011;Rodriguez et al, 2010). Alarming percentage of osteolysis has been reported with total ankle arthroplasty before (Doets et al, 2006;Knecht et al, 2004;Pyevich et al, 1998;Schutte & Louwerens, 2008;Su et al, 2004;Valderrabano et al, 2004;Wood & Deakin, 2003). On the other hand, some authors have reported the opposite and bone mineral density has been shown to increase adjacent to hydroxyapatite coated ankle arthroplasty (Zerahn et al, 2000, Zerahn & Kofoed, 2004.…”
Section: Total Ankle Replacement and Osteolysissupporting
confidence: 59%
“…Other reports with similar findings have been published afterwards (Besse et al, 2009;Besse et al, 2010;Kokkonen et al, 2011;Rodriguez et al, 2010). Alarming percentage of osteolysis has been reported with total ankle arthroplasty before (Doets et al, 2006;Knecht et al, 2004;Pyevich et al, 1998;Schutte & Louwerens, 2008;Su et al, 2004;Valderrabano et al, 2004;Wood & Deakin, 2003). On the other hand, some authors have reported the opposite and bone mineral density has been shown to increase adjacent to hydroxyapatite coated ankle arthroplasty (Zerahn et al, 2000, Zerahn & Kofoed, 2004.…”
Section: Total Ankle Replacement and Osteolysissupporting
confidence: 59%
“…The use of TAA as an alternative to ankle fusion is continuously expanding, but reported results have been limited to small patient numbers and shortterm followups. An important concern regarding TAA is the high rate of intraoperative complications [20,27,31,35] and high rate of reoperations after this procedure [36]. We therefore determined (1) the intraoperative and postoperative complications, including surgical revision for any reason; (2) the prosthesis component stability; (3) whether TAA provides pain relief in the midterm; and (4) the midterm functional outcome, including ROM and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although TAA is becoming more commonly used, the relative benefits of TAA continue to be one of the most debated topics in foot and ankle surgery [11]. First, there is a steep learning curve associated with performing TAA [20,27,31,35]. Intraoperative complications are common and include medial or lateral malleolar fractures and lacerations to the tendons (posterior tibial tendon, flexor digitorum/hallucis longus), and nerves (deep peroneal nerve, superficial peroneal nerve) [20,27,31,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, osteolysis has been noted in some studies and in vitro simulator studies have shown wear debris to be generated. Revision surgery involves replacing the implant, or, in many cases, performing an ankle fusion [37,38].…”
Section: Ankle Joint Replacementmentioning
confidence: 99%